If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -6k = 6(1 + 2k) -18 + -6k = (1 * 6 + 2k * 6) -18 + -6k = (6 + 12k) Solving -18 + -6k = 6 + 12k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-12k' to each side of the equation. -18 + -6k + -12k = 6 + 12k + -12k Combine like terms: -6k + -12k = -18k -18 + -18k = 6 + 12k + -12k Combine like terms: 12k + -12k = 0 -18 + -18k = 6 + 0 -18 + -18k = 6 Add '18' to each side of the equation. -18 + 18 + -18k = 6 + 18 Combine like terms: -18 + 18 = 0 0 + -18k = 6 + 18 -18k = 6 + 18 Combine like terms: 6 + 18 = 24 -18k = 24 Divide each side by '-18'. k = -1.333333333 Simplifying k = -1.333333333
| 17x=16x-24 | | 7(2x+3)=7 | | 5y+2(y-2)=7y-2(y-10) | | 17x=16x | | x/12=x/4-2 | | E=lR | | 44=-u+188 | | 18x+64=19x | | x/5=x/6-3 | | 0x^2-71x-9=0 | | 106=161-w | | 4x^2-13x+3x=0 | | (15/x)=((x^2)-7x+17) | | -v+111=202 | | 1/3+7/8+4/5 | | -x+279=208 | | 3x-6(x+1)=-3x+19 | | 21/5(-13/4p+5)=651/5 | | X(6x-3)=(6x+9)(x-8) | | -4(5y-7)-y=-2(y-5) | | x*y=630 | | x(2x+3)=4 | | 3(x-8)=9x | | 3x+9-2x=13 | | 4x^4-20x^2+16=0 | | 26x+12=5(5x+4) | | 10-(2*-4)+3x=16 | | (5u+3)(5-u)=0 | | 3x+9-2x=14 | | 2x-6x+9=x-6+15 | | (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 |